Proposição de gestão de resíduos sólidos para uma comunidade quilombola: estudo de caso da Vila Nova Jutaí, Breu Branco-PA - FREITAS, Giselle do Socorro Pinto de (2023)
One of the main concerns linked to sustainability refers to the increase in the generation of solid waste, traditional communities such as the quilombolas, suffer from these direct and indirect environmental impacts resulting from unsustainable practices of managing this waste and the pollution they generate in these places. This study aimed to propose management measures for household solid waste generated in the quilombola community Vila Nova Jutaí, located in the municipality of Breu Branco-PA. In this sense, 100 questionnaires prepared based on theoretical assumptions about the subject of study were applied. In the field research, of a descriptive and qualitative nature, it was noticed that the public power performs a waste collection service in the community and that part of the residents, despite being aware of the problems caused by the incorrect destination given to the generated waste, still performs it. In addition, it was found that the majority of the surveyed population does not receive guidance on how to properly treat the waste generated, nor does it receive incentives for such actions. This scenario pointed to the need for investments in incentive programs for selective collection and composting to build an individual and collective awareness of changes in habits. However, for these measures to be carried out satisfactorily and for them to contribute to improving the quality of life of community residents, continuous awareness is needed to ensure the effectiveness of these practices at the local level.